1993
DOI: 10.1148/radiology.186.1.8416569
|View full text |Cite
|
Sign up to set email alerts
|

Osteoid osteomas of the femoral neck: report of four cases evaluated with isotopic bone scanning, CT, and MR imaging.

Abstract: Four patients, ranging in age from 6 to 32 years, with surgically proved parosteal lesions of the femoral neck are presented. In one case, magnetic resonance (MR) imaging was the initial study ordered prior to plain radiography, and in three cases MR imaging was performed after plain radiography. Findings in the MR images were abnormal in all four cases; however, the nidus was not identified prospectively. Incorrect diagnoses based on findings at MR imaging of secondary marrow edema and/or synovitis included E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 0 publications
2
44
0
3
Order By: Relevance
“…No cases associated with synovitis in the adjacent joints have been reported in which the nidus is located in diaphysis of the long bones. Surgical removal of the nidus has been reported to result in remission of synovitis (10,27). As previously reported, in our control Cases 5 to 7, diaphyseal lesions were not associated with synovitis.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…No cases associated with synovitis in the adjacent joints have been reported in which the nidus is located in diaphysis of the long bones. Surgical removal of the nidus has been reported to result in remission of synovitis (10,27). As previously reported, in our control Cases 5 to 7, diaphyseal lesions were not associated with synovitis.…”
Section: Discussionsupporting
confidence: 85%
“…CassarPullicino et al (9) reported that synovitis in the involved joint occurred in 25% of tumors evaluated by surgical findings. Magnetic resonance imaging (MRI) showed pooling of joint effusion in all cases of intraarticular OO (10). Histologic examination further confirmed the presence of prominent nonspecific chronic synovitis or lymphofollicular synovitis, resembling rheumatoid arthritis (RA), in the joint with intraarticular OO (11).…”
mentioning
confidence: 87%
“…2,31 Juxtanidal marrow oedema is variable; a more pronounced marrow reaction may occur in younger patients. 32 The subtle radiographic appearance combined with the non-specific clinical presentation of intra-articular osteoid osteomas often leads to a delayed diagnosis. 23,33,34 Patients have been reported to have had symptoms for 8 -43 months before the osteoid osteoma is found.…”
Section: Figure 2: Osteoid Osteoma Of the Right Femoral Neck (A) It mentioning
confidence: 99%
“…CT scan is the gold standard for diagnosis; it can clearly identify the nidus, its extension, and is very helpful in differential diagnosis [12]. The use of MRI is controversial since it often fails to identify the nidus, and because of intramedullary oedema it can lead to misdiagnosis (other aggressive or malignant tumors, osteonecrosis or stress fractures) [13,14]. Differential diagnoses include: osteoblastoma, stress fracture, abscess, intracortical osteosarcoma, enostosis [15].…”
Section: Introductionmentioning
confidence: 99%